Playing the city. Childhood, play and space in team 10’s manifesto images - Albanelli, Michele (2023)
The article examines the capacity of play to produce collective space, with the aim of highlighting its relevance and potential in the field of architecture. The interpretative reading of images and diagrams produced in the framework of the last three editions of CIAM (1953, 1956 and 1959) by Team 10 members, Aldo van Eyck and Alison and Peter Smithson, serves as a premise for placing the aforementioned objective in a disciplinary context. Through a historical-comparative research methodology that links the main objects of study with references and experiences from various disciplinary fields (with particular emphasis on the field of education), we proceed with the analysis of the images, identifying and proposing four conceptual axes that can be transferred to the contemporary work of architects: the celebration of the everyday, the use of the participatory language of urban photography, the understanding of the street as a stage for life, and the value of play in the production of collective space. Under the aforementioned premises, the text opens the possibility and the debate towards the integration of play as an index of valuation and projection of built space, highlighting, 70 years after CIAM (1953), the validity of the ideas of Team 10 and the disciplinary relevance of the multiple ways of doing architecture that the avant-garde group proposes through its individual and collective operations.